PENERAPAN COOPRATIVE LEARNING TIPE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA SUBTEMA KEBERSAMAAN DALAM KEBERAGAMAN - Rahmatdani, Sukmah; Kartika Rini, Ayu (STKIP Subang, 2017)
This study aims to improve student learning outcomes by using model Cooperative Learning type Mind Mapping on the theme of togetherness togetherness subtema in Diversity. This research was conducted in the class IV D SDN Komplek Karang Taruna Sari and background of the students who showed less result of study which still low and many criteria of minimal mastery because teacher often use lecture motto which tend to monoton and not yet using model Cooperative Learning Type Mind Mapping which consist of 5 Phases of conveying goals and motivating students, presenting information, organizing students into study groups, guiding study and work groups, and evaluating. Assessment used in this research is Pretest and Posttest test technique to know student learning result of cognitive assessment, attitude assessment, making mind mapping and observation sheet to know teacher and student attitudes during learning process. The results showed an increase in the average of the assessment of learning outcomes. On the cognitive assessment of the average value of cycle I is 69 while the second cycle reached 72.5 and the third cycle reached 74, on the affective assessment of the average value of cycle I is 61 while the second cycle reached 63 and the third cycle reached 74. This shows that the use of model Cooperative Learning Type Mind Mapping can improve student learning outcomes on the theme of togetherness kebersamaa subtema in the diversity of class IV D SDN Komplek Karang Taruna Sari. Thus, the use of Cooperative Learning type Mind Mapping model can be used as one of the learning models to be applied to thematic learning with other themes and subthemes.